New species and distributional records of Sericini from groundnut ecosystem in South India (Coleoptera: Scarabaeidae: Sericinae) - Jayashree, Selvaraj; Sreedevi, Kolla; Ahrens, Dirk (Zootaxa, 2026)
The present paper presents the results of surveys of groundnut (Arachis hypogaea L.) cultivations in India with respect to Sericinae of Scarabaeidae (Coleoptera). Two new species of Sericini are described: Neoserica telangana Jayashree, Sreedevi & Ahrens, sp. nov. and Maladera rampurensis Jayashree, Sreedevi & Ahrens, sp. nov. Additionally, new records of known species are given including first state records for eight species of Sericini from Telangana and three species from Andhra Pradesh. The habitus and genitalia of the new species are furnished with detailed illustrations.